Collisions in soccer kicking - Bull Andersen, T.; Dörge, H. C.; Thomsen, F. I. (Sports Engineering, 1999)
An equation to describe the velocity of the soccer ball after the collision with a foot was derived. On the basis of experimental results it was possible to exclude certain factors and only describe the angular momentum of the system, consisting of the shank, the foot and the ball, leading to an equation that was simple and useful. Furthermore, it was found that the main reasons for changes in ball velocity are the velocity of the foot before impact and the coefficient of restitution. The mass of the shank-foot segment does not influence the velocity of the ball significantly.